Forecasting Number of Legal Violations in Indonesian Sea Using the Fuzzy Double Exponential Smoothing Method - Hozairi; Syariful Alim; Marcus Tukan (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
Maritime security in Indonesia is an indicator of the success of the Government in managing the sovereignty of the State because two-thirds of Indonesia is sea, so Indonesia is called a maritime country. This study aims to predict the number of law violations in Indonesian seas. Predicting events is a strategic step to set the next security operation strategy. The method used to predict violations of law at sea in Indonesia is Fuzzy Double Exponential Smoothing, the Fuzzy method is used to normalize violation data and the Double Exponential Smoothing method is used to predict future events, a combination of fuzzy and double exponential smoothing methods was developed to improve some previous research which only use exponential smoothing only in making predictions. The data processed is data on violations of law at sea in Indonesia from 1996 to 2019 from the Indonesian Maritime Security Agency. The results obtained from this study are the data smoothing constant value (α = 0.81), the trend smoothing value (γ = 0.08), the mean absolute percentage error value (MAPE = 21.78%) and the root mean value average error (RMSE = 60.72). The results of this study predict that the number of violations of law at sea in Indonesia in 2020 will decrease to 98 cases, this is due to several factors, including the focus of the Government on carrying out security operations in Indonesian seas in an integrated manner involving many institutions. The research contribution can be considered by Indonesian Maritime Security Agency to improve Indonesia's maritime security by involving institutions that have legal authority in Indonesian seas